The geochemical gas field in surface sediments in the Southwest sub-basin of East Vietnam Sea: distribution, origin, and comparative features with other regions of Western East Vietnam Sea - Le, Duc Luong; Nguyen, Hoang; Obzhirov, Anatoly; Shinjo, Ryuichi; Shakirov, Renat B. (Vietnam Journal of Marine Science and Technology, 2022)
We analyzed 39 gas samples, including carbon dioxide, hydrocarbon gases C1–C4, hydrogen, and helium, in surface sediment from 19 gravity cores collected from the SW sub-basin of the East Vietnam Sea (EVS) using the headspace and vacuum degassing methods. Based on the result, we discussed the distribution and origin of gases in the southwest sub-basin EVS surface sediments. The sediments are mostly clay and silty clay containing methane ranging from 0.5–440 ppm. The anomalous concentrations of methane, helium, and hydrogen occur along the continental slope in the Nam Con Son basin of Southwest EVS. Methane is the dominant gas compared to other detected hydrocarbon gases, including ethylene, propane, and butane. Based on comparative results, the background methane concentrations in surface sediments decrease from South to North, from the southwestern sub-basin of the East Vietnam Sea to the Phu Khanh and the Red river basins. We propose the presence of a large-scale degassing zone of hydrocarbon gases and discuss the gases’ origin in surface sediments based on hydrocarbon gas ratios, carbon isotope compositions of carbon dioxide and methane, and the relationship between geochemical characteristics of surface sediments and fault system, and surface sediment gases.